NARSISME MAHASISWA ILMU KOMUNIKASI UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR DI MEDIA SOSIAL INSTAGRAM - Hatta, Harmin; Udiawati Anwar; Muliaty Amin (Rumah Jurnal STAIN Majene, 2023)
This article aims to find out the forms of narcissism on Instagram social media, the impact of narcissism via Instagram social media for Communication Science Students at UIN Alauddin Makassar. The type of research used is qualitative with a phenomological approach. Data collection methods are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results show: 1) Narcissism of Communication Science Students at UIN Alauddin Makassar on social media Instagram with the characteristics of exaggerating their achievements and talents and feeling like they are a great person, feeling entitled to special treatment from others, exploiting interpersonal relationships, looking down on them. other people, preoccupied with success, beauty, brilliance. 2) The impacts caused by narcissistic behavior consist of two, namely positive impacts and negative impacts. Positive impacts include, becoming famous, having lots of friends, increasing self-confidence. Meanwhile, the negative impact is making other people uncomfortable, appearing heterodox, showing falsehood. Conclusions and suggestions for students to be wiser in using Instagram social media so that narcissism can be reduced. Students are expected to reduce their use of social media Instagram and it would be better to keep themselves busy with good things such as the academic world, organizations or joining communities so that what they post is more mature and useful for other people. Keywords: Narcissism, Students Instagram